Immense reliance on natural resources and environmental challenges in G-20 economies through the lens of COP-26 targets. (December 2022) - Lei, Xiying; Yang, Yao; Alharthi, Majed; Rasul, Farhat; Faraz Raza, Syed Muhammad
Abstract: The present study investigates how extensive utilization of natural resources drags away G-20 nations from the targets of carbon control proposed in COP-26. In this study, panel data for G-20 countries is taken from 1991 to 2019. The study uses cross sectional CS-ARDL to examine relation among carbon emissions and natural resource consumption. The results of this study reveals, the relation is positive between environmental degradataion and natural resource consumption. It has been observed that an increase in the share of rent received from the consumption of mineral resources, forest resources, oil, and natural gas to Gross Domestic Product (GDP) is causing serious environmental hazards like a tremendous increase in emissions of CO2 . Furthermore, the empirical outcomes for the study has depicted U-shape which is in inverted form for the two variables which are Carbon emissons and economic growth, this relation also confirms the hypothesis of (EKC) Environmental Kuznets Curve for G-20 countries. Finally, suitable recommendations are made to achieve the targets of COP-26 by controlling the massive consumption of natural resources in G-20 economies. Highlights: Use of natural resources is putting G20 countries far from COP-26 targets. Rent from forest resources is increasing environmental challenges in G20 nations. The rent obtained from mineral resources and oil extraction is stimulating CO2 emissions. High reliance on natural gas rent increasing environmental issues in G20 Countries. The intelligent use of natural resources is inevitable to attain COP-26 targets.